Robotic Major Hepatectomy: Influence of Age on Clinical Outcomes. Issue 1 (January 2021) - Sucandy, Iswanto; Luberice, Kenneth; Rivera-Espineira, Gabriel; Krill, Emily; Castro, Miguel; Bourdeau, Timothy; Ross, Sharona; Rosemurgy, Alexander
Background: This study was undertaken to determine if age influences postoperative outcomes for patients undergoing robotic major hepatectomy. Methods: Ninety-four patients undergoing robotic major hepatectomy were prospectively followed. With regression analysis, demographic data and postoperative outcomes were compared to age. Data are presented as median (mean ± SD). Results: Overall, the patients were of age 62 (61 ± 13) years, body mass index (BMI) of 29 (29 ± 5.9) kg/m 2, and American Society of Anesthesiologists (ASA) class of 3 (3 ± 0.5). The mass size was 5 (5 ± 3.0) cm. The operative duration was 252 (276 ± 106) minutes with an estimated blood loss (EBL) of 175 (249 ± 275.9) mL. One operation was converted to "open" due to bleeding, accounting for the only intraoperative complication. Nine patients required intensive care unit (ICU) admission. Postoperatively, 7 patients had complications with no in-hospital mortalities, and a length of stay (LOS) of 4 (5 ± 2.6) days. Thirteen patients were readmitted within 30 days with 0 deaths within 30 days. A significant relationship was found between age and ASA class ( P = .001) and LOS ( P = .03). No correlation was found when comparing age to operative duration, EBL, ICU admission, ICU duration, complications, and readmission within 30 days. Conclusion: For patients undergoing robotic major hepatectomy, there was no significant correlation between age and perioperative outcomes, with the exception of LOS. Increasing age is not associated with increased morbidity or perioperative mortality. With the application of innovative technology, that is, the robotic approach, surgeons should be encouraged to undertake major hepatectomy in elderly patients deemed candidates for surgery.